50h=60h

Simple and best practice solution for 50h=60h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 50h=60h equation:


Simplifying
50h = 60h

Solving
50h = 60h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-60h' to each side of the equation.
50h + -60h = 60h + -60h

Combine like terms: 50h + -60h = -10h
-10h = 60h + -60h

Combine like terms: 60h + -60h = 0
-10h = 0

Divide each side by '-10'.
h = 0.0

Simplifying
h = 0.0

See similar equations:

| -x-2y=7 | | 10x^2+36=0 | | 16-2w=10w-2-6w | | 3x-9y-8x+5y= | | -10=9k-Pr | | (-4+x)10=2x | | 625-a^4=0 | | 150+.10x=167 | | 15a-54=-89 | | 15x^2-6x=3x | | 2.5q-4.8-4.6q=-3.1q-2.7 | | X+(2A)+(B+2ft)=70 | | 5x+15=9-5(4x+4) | | 2.5q-4.8-4.6q=3.1q-2.7 | | y^4+6y-256=0 | | 34+10x=20+12x | | 4.9q-2.8-4.5q=0.6q-3.4 | | 3(2x+5)-15=4x+3.2-8x | | -2[5x]=18 | | -13=3x-4 | | 4x-9=12-3x | | -17+-2x=6-x | | 3[w]+15=9 | | 2[x]+7=21 | | 4h+10=6h+2 | | 4.9q-2.8-4.5q=-0.6q-3.4 | | 15x+26=236 | | [5-2y]+3=8 | | x^3-7x^2-168x+720=0 | | [2w+1]-3=2 | | y-1=.25 | | -.875-(-n)=-.58 |

Equations solver categories